Comb-assisted mercury spectroscopy in the deep-ultraviolet: towards the development of a new primary thermometer. Issue 1 (1st January 2023) - Gravina, S; Clivati, C; Chishti, N A; Castrillo, A; Fasci, E; Bertiglia, F; Lopardo, G; Sorgi, A; Coluccelli, N; Galzerano, G; Cancio Pastor, P; Levi, F; et al.
Abstract: We report on the development of a new primary thermometer based upon high-precision spectroscopy of mercury vapors in the deep-ultraviolet region for the practical realization of the new kelvin. The line profile of the (6 s 2 ) 1 S 0 → (6 s 6 p ) 3 P 1 intercombination transition of the 200 Hg bosonic isotope is observed with a high spectral fidelity using a coherent radiation source at 253.7 nm. This latter consists of a near-IR external cavity diode laser followed by a double-stage second-harmonic generation apparatus. Metrology grade UV spectroscopy is demonstrated by locking the diode laser to a self-referenced optical frequency comb synthesizer.